2005
DOI: 10.1002/mnfr.200500022
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as an anti-inflammatory and anti-aging agent: Mechanisms and clinical implications

Abstract: Resveratrol is a phytoalexin polyphenolic compound found in various plants, including grapes, berries, and peanuts. Multiple lines of compelling evidence indicate its beneficial effects on neurological, hepatic, and cardiovascular systems. Also one of the most striking biological activities of resveratrol soundly investigated during the late years has been its cancer-chemopreventive potential. In fact, recently it has been demonstrated that this stilbene blocks the multistep process of carcinogenesis at variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
383
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(388 citation statements)
references
References 206 publications
(197 reference statements)
3
383
0
2
Order By: Relevance
“…antioxidative or anti-inflammatory properties, protection against cardiovascular diseases, and chemopreventive effects, have been attributed to trans-resveratrol thus far. Several different molecular targets, including inhibition of cyclooxygenases 1 and 2, inhibition or stimulation of nitric-oxide synthases, and activation of adenylyl and guanylyl cyclase, have been discussed in connection with these different effects (21,22,44). The resveratrol concentrations required to achieve most of these different effects in the respective experimental systems have been shown to range from 5 to 100 M or sometimes even higher (21).…”
Section: Discussionmentioning
confidence: 99%
“…antioxidative or anti-inflammatory properties, protection against cardiovascular diseases, and chemopreventive effects, have been attributed to trans-resveratrol thus far. Several different molecular targets, including inhibition of cyclooxygenases 1 and 2, inhibition or stimulation of nitric-oxide synthases, and activation of adenylyl and guanylyl cyclase, have been discussed in connection with these different effects (21,22,44). The resveratrol concentrations required to achieve most of these different effects in the respective experimental systems have been shown to range from 5 to 100 M or sometimes even higher (21).…”
Section: Discussionmentioning
confidence: 99%
“…19 In the human setting, we have demonstrated that fetuses exposed to a maternal diet rich in polyphenols in the third trimester show higher ductal velocities and lower pulsatility indexes (PIs), as well as larger right ventricles, than those exposed to minimal amounts of these substances. 15,16 The rationale for understanding the behavior of fetal ductal arteriosus flow dynamics after maternal ingestion of PRF in late pregnancy is that these substances have definite anti-inflammatory and antioxidant effects, largely reported in the literature, [20][21][22][23][24][25][26][27][28][29] based on the inhibition of cyclooxygenase-2 or other components of the metabolic cascade resulting in prostaglandins biosynthesis. These actions are similar to that involved in prostaglandin inhibition caused by NSAID.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is abundant in red wine with concentrations ranging from 10 to 20 M [6,7]. The works show that Resveratrol is rapidly absorbed and metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol was further demonstrated to be an antitumor and chemopreventive agent; and found to affect cellular proliferation through its action on tumor initiation, promotion, and progression [5,6]. These properties have been explained mainly by its activities in cell cycle control and apoptosis induction [7,8].…”
Section: Introductionmentioning
confidence: 99%